2004
DOI: 10.1108/eb022920
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Negotiation: The Tension Between Creating and Claiming Value

Abstract: As a departure from past research on emotional intelligence (EI),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(34 citation statements)
references
References 48 publications
2
31
1
Order By: Relevance
“…The observed results of the current study encourage to continue extending previous study of EI in negotiation context (e.g., Der Foo et al, 2004) also to other work life interactions and to study particular forms of emotional expressions, as suggested by Morris and Keltner (2000).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The observed results of the current study encourage to continue extending previous study of EI in negotiation context (e.g., Der Foo et al, 2004) also to other work life interactions and to study particular forms of emotional expressions, as suggested by Morris and Keltner (2000).…”
Section: Discussionsupporting
confidence: 70%
“…Building upon the work on negotiation by Der Foo et al (2004), we suggest that high trait EI assists both the manager and the subordinate in conducting a performance review discussion, by helping in controlling one’s own emotions, detecting emotions of the partner, and expressing own emotions appropriately. We follow the suggestions of Morris and Keltner (2000) in studying particular forms of emotional expression, smiling and frowning, during dyadic interaction between a manager and a subordinate.…”
Section: Current Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the effectiveness of the negotiation process and its relationship to EI, Foo, Elfenbein, Tan, and Aik (2004) carried out a series of laboratory experiments in which individuals negotiated in pairs. These experiments reveal that individuals with high EI reported their negotiation experience more positively.…”
Section: Ei and Negotiationmentioning
confidence: 99%
“…Integrative negotiation, also referred to as a "creating value" strategy, is a mutual process of discovering the other actors' interests, developing new and often wider problem definitions, employing problem-solving behaviour and searching for ways to increase the total benefit (Der Foo, Elfenbein, Tan, & Aik, 2004;Leeuwis, 2000;Sebenius, 1992). In contrast, distributive negotiation refers to dividing or apportioning scarce and fixed resources among the negotiators (Thompson, Wang, & Gunia, 2010).…”
Section: Introductionmentioning
confidence: 99%